Individualized gray matter morphological abnormalities unveil two neuroanatomical obsessive-compulsive disorder subtypes - Baohong Wen; Keke Fang; Qiuying Tao; Ya Tian; Lianjie Niu; Wenqing Shi; Zijun Liu; Jin Sun; Liang Liu; Xiaopan Zhang; Ruiping Zheng; Hui-Rong Guo; et al. (Translational Psychiatry)
Abstract Obsessive-compulsive disorder (OCD) is a highly heterogeneous disorder, with notable variations among cases in structural brain abnormalities. To address this heterogeneity, our study aimed to delineate OCD subtypes based on individualized gray matter morphological differences. We recruited 100 untreated, first-episode OCD patients and 106 healthy controls for structural imaging scans. Utilizing normative models of gray matter volume, we identified subtypes based on individual morphological abnormalities. Sensitivity analyses were conducted to validate the reproducibility of clustering outcomes. To gain deeper insights into the connectomic and molecular underpinnings of structural brain abnormalities in the identified subtypes, we investigated their associations with normal brain network architecture and the distribution of neurotransmitter receptors/transporters. Our findings revealed two distinct OCD subtypes exhibiting divergent patterns of structural brain abnormalities. Sensitivity analysis results confirmed the robustness of the identified subtypes. Subtype 1 displayed significantly increased gray matter volume in regions including the frontal gyrus, precuneus, insula, hippocampus, parahippocampal gyrus, amygdala, and temporal gyrus, while subtype 2 exhibited decreased gray matter volume in the frontal gyrus, precuneus, insula, superior parietal gyrus, temporal gyrus, and fusiform gyrus. When considering all patients collectively, structural brain abnormalities nullified. The identified subtypes were characterized by divergent disease epicenters. Specifically, subtype 1 showed disease epicenters in the middle frontal gyrus, while subtype 2 displayed disease epicenters in the striatum, thalamus and hippocampus. Furthermore, structural brain abnormalities in these subtypes displayed distinct associations with neurotransmitter receptors/transporters. The identified subtypes offer novel insights into nosology and the heterogeneous nature of OCD.